2021
DOI: 10.21203/rs.3.rs-777954/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fine Mapping of Intracranial Aneurysm Susceptibility Based on a Genome-wide Association Study

Abstract: In addition to conventional genome-wide association studies (GWAS), a fine-mapping is increasingly used to identify the genetic function of variants associated with disease susceptibilities. Here, we used a fine-mapping approach to evaluate the casual variants based on a previous GWAS involving patients with intracranial aneurysm (IA). Fine-mapping analysis was conducted based on the chromosomal data provided by GWAS consisting 250 patients diagnosed with IA and 296 controls using posterior inclusion probabili… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…They identified (PLOD3 c.1315G>A, NTM c.968C>T and CHST14 c.58C>T) as any significant copy number variants in the family (38). In one other study, based on chromosomal data from genome-wide association studies (GWAS) of 250 patients diagnosed with IA and 296 controls, our fine mapping analysis showed that four functional candidate variants, GBA, TCF24, OLFML2A and ARHGAP32, were associated with susceptibility and pathogenesis of IA (39). and the presence of the T allele in the rs12976445 polymorphism was associated with a lower risk of IA rebleeding (40).…”
Section: Discussionmentioning
confidence: 72%
“…They identified (PLOD3 c.1315G>A, NTM c.968C>T and CHST14 c.58C>T) as any significant copy number variants in the family (38). In one other study, based on chromosomal data from genome-wide association studies (GWAS) of 250 patients diagnosed with IA and 296 controls, our fine mapping analysis showed that four functional candidate variants, GBA, TCF24, OLFML2A and ARHGAP32, were associated with susceptibility and pathogenesis of IA (39). and the presence of the T allele in the rs12976445 polymorphism was associated with a lower risk of IA rebleeding (40).…”
Section: Discussionmentioning
confidence: 72%
“…In this study, we aimed to investigate gene-gene interaction using the previous GWAS data for Korean patients with IA for the first time 11) . However, due to the relative small number of the enrolled patients and possible false positives 14) , we did not perform all possible pairwise SNP-SNP interaction and inevitably focused on two IA candidates of BOLL and EDNRA by referring to previous studies 12,13) . Nevertheless, we required further replication GWAS and exhaustive searching for SNP-SNP interaction in a large dataset of GWAS 19) .…”
Section: Discussionmentioning
confidence: 99%